A Fundamental Transformation of Sustainable Business Model: Roles of Islamic Banking in Accelerating MSMEs Industry - Dini Maulana Lestari; Reni Furwanti (International Journal of Islamic Finance, 2026)
Abstract Background: This study analyses the role of Islamic banking in supporting and accelerating MSMEs industry in Indonesia, remembering this industry holds a significant role in sustaining Indonesia’s national economic growth. Nevertheless, several challenges remain steady such as limited access to financial products, lack of financial and digital literacy and so ford making this industry difficult to be agile. Objectives: This study aims to examine and analyse the role of ESG at Islamic banking industry in Indonesia to boost the portion of financing for MSMEs by considering the role of green bond as moderating variable. Novelty: This study tries to examine the ESG performances by integrating it with moderating effect of green bond, remembering that most previous researches only focuse on financial performance of Islamic banking industry to increase its’ contribution for MSMEs agility. Research Methodology / Design: This is explanatory research with quantitative approach and documentation method, employing panel data from 15 Islamic banks registered by Otoritas Jasa Keuangan from 2020-2024 as the main sample, obtaining from annual report. Furthermore, Moderated Regression Analysis (MRA) is used to analyse the data and figure out the most suitable estimation model. Findings: The finding reveals that environmental performance shows negative impact in to increase the amount of financing for MSMEs. However, the other performances such as social and governance show conversely. Implication: The result is expected to shed the light the essential role of ESG and green bonds representing the goals of Indonesia Sustainable Finance Taxonomy to support sustainable finance behavior among Islamic banking industry as financial institution and MSMEs enhancing national economic growth.